Vitamin-C enriched kalamansi (Citrus micro carpa Bunge) syrup - Lim Bee Ling, Yvonne Y.
Thje study hoped to determine the optimum ratio of kalamansi juice to 60°Bx to produce a kalamansi syrup of high acceptability. Pasteurized kalamansi juice was mixed with the syrup at varying proportions: 20:100, 30:100, 40:100 and 50:100 ml juice:ml syrup. The ratio that gave the most desirable flavor blend based on general acceptability ratings, retention of the characteristic kalamansi flavor and the right blend of sweet and sour was used in the second phase of the study. For this study, the 40:100 ratio was selected. The second phase included fortification, sulfiting and the study of storage quality of the product under accelerated temperature of 37°C. The ascorbic acid content of the kalamansi syrup was very low after processing, implying that both pasteurization and syrup dilution caused its destruction. Fortification of the syrup ascorbic acid improved its flavor and at the same time increase its nutritive value. Sulfiting as a treatment did not affect pH value, nor did it exert any appreciable change in soluble solids and titratable acidity of the product. On storage, it appeared that sulfiting could have produced a slight bleaching effect considering that no browning was observed in the sulfited samples. Storage at 37°C was expected to accelerate changes in the kalamansi syrup itself within a period of one month. Results indicated that pH, titratable acidity and soluble solids contents were not significantly affected within the storage period inspite of the high storage temperatur